PENGARUH PEMBERDAYAAN DANA ZAKAT PRODUKTIF SEBAGAI MODAL USAHA UMKM TERHADAP KINERJA UMKM (Studi pada BAZNAS) - Fikri Charfian Hadi Pratama Kusuma; Iswan Noor (Islamic Economics and finance in Focus, 2023)
This study aims to determine the factors that influence the performance of MSMEs in Tanah Abang, Central Jakarta in 2022. The research data was obtained by distributing questionnaires to mustahiq productive zakat recipients. Human Resources performance variable in MSMEs as the dependent variable. The variable Provision of Productive Zakat Funds, Productive Zakat Fund Management System, and Productive Zakat Fund Utilization System as independent variables. This study uses data analysis methods in the form of Classical Assumption Tests and Multiple Linear Regression Tests. The results of this study indicate that partially, the variables X1, X2, and X3 have no significant effect on Y. Meanwhile, simultaneously, the variables X1, X2, and X3 significantly affect Y.